(untitled) (European Journal of Education and Psychology, 2009)
The aim of this paper is to determine the level of agreement with a series of stereotypes present in our society. These stereotypes are related to sexuality, personality, and cognitive aspects in old people. A sample of 806 people was divided into four groups: youths and older people who had some gerontology education and youths and older people without gerontology education. The analysis carried out shows that gerontology education is extremely relevant to avoid erroneous beliefs about old people. The results reveal the low degree of agreement with the statements: Impotence is usually psychological, but in old men, it is due to age; Old people do not benefit much from education due to their cognitive deficits; Intelligence peaks around the age of 30 and then declines gradually; Sooner or later, old people become senile; Senile people cannot be helped by psychotherapy; Personality is relatively stable in adulthood; and Menopause causes nervous breakdowns. Key words: Beliefs, youths, elderly, gerontology education.